Two Bombyx mori acetylcholinesterase genes influence motor control and development in different ways - Xinhai Ye (Nature Portfolio, 2017)
Abstract Among its other biological roles, acetylcholinesterase (AChE, EC 3.1.1.7), encoded by two ace in most insects, catalyses the breakdown of acetylcholine, thereby terminating synaptic transmission. ace1 encodes the synaptic enzyme and ace2 has other essential actions in many insect species, such as Chilo suppressalis and Plutella xylostella. The silkworm, Bombyx mori, has been domesticated for more than two thousand years and its aces have no history of pesticide exposure. Here, we investigated the functional differences between two ace genes, BmAce1 and BmAce2, in the silkworm. qPCR analysis indicated that BmAce1 is highly expressed in muscle and BmAce2 is more ubiquitously expressed among tissues and enriched in the head. Both genes were separately suppressed using chemically synthesized siRNAs. The mRNA abundance of the two ace genes was significantly reduced to about 13% – 75% of the control levels after siRNA injection. The AChE activities were decreased to 32% to 85% of control levels. Silencing BmAce2 resulted in about 26% mortality, faster and higher than the 20% in the siBmAce1-treated group. Silencing BmAce1 impacted motor control and development to a greater extent than silencing BmAce2, although both treatment groups suffered motor disability, slowed development and reduced cocoons. Both genes have essential, differing biological significance.